2004
DOI: 10.1194/jlr.m300409-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

The steroidal analog GW707 activates the SREBP pathway through disruption of intracellular cholesterol trafficking

Abstract: Recently, a new class of lipid-lowering agents has been described that upregulate LDL receptor (LDLr) activity. These agents are proposed to activate sterol-regulated gene expression through binding to the sterol regulatory element binding protein (SREBP) cleavage-activating protein (SCAP). Here, we show that the steroidal LDLr upregulator, GW707, induces accumulation of lysosomal free cholesterol and inhibits LDL-stimulated cholesterol esterification, similar to that observed in U18666A-treated cells and in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…The lysosomal sequestration of LDL- derived cholesterol affects efflux activity by limiting cholesterol substrate for ABCA1-dependent efflux and by failing to appropriately generate LDL-cholesterol-derived side-chain oxysterols (15,17,18). In Npc1 -/-cells, decreased production of side-chain oxysterols, which serve as endogenous LXR ligands, results in reduced ABCA1 protein expression and lower cholesterol efflux activity (16,24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lysosomal sequestration of LDL- derived cholesterol affects efflux activity by limiting cholesterol substrate for ABCA1-dependent efflux and by failing to appropriately generate LDL-cholesterol-derived side-chain oxysterols (15,17,18). In Npc1 -/-cells, decreased production of side-chain oxysterols, which serve as endogenous LXR ligands, results in reduced ABCA1 protein expression and lower cholesterol efflux activity (16,24).…”
Section: Discussionmentioning
confidence: 99%
“…Previously we showed that the sterol homeostatic defects in NPC1 mutant cells were associated with a profound decrease in synthesis of LDL-cholesterol-derived oxysterols (17,18). To assess whether decreased production of 27-HC, an endogenous LXR ligand, causes reduced LXR-mediated cholesterol efflux, we measured oxysterol production in peritoneal macrophages in response to acetylated LDL (AcLDL) cholesterol loading.…”
Section: Generation Of Mice With Deletion Of Npc1 In Bm-derived Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, targeting several of these pathways would likely be more beneficial than targeting a single pathway. For example, NP-C mice fail to use lipoprotein-derived cholesterol for synthesis of 25-and 27-hydroxycholesterol (Frolov, et al, 2003,Zhang, et al, 2004. These compounds are ligands for the liver X receptor (LXR) that promote cellular cholesterol efflux and catabolism.…”
Section: Mechanism Of Allopregnanolone Action: Gaba a Receptormentioning
confidence: 99%
“…2 was not signifi cantly different from that observed for the wild-type (circles) in both the magnitude of the 27-HC biosynthetic response and in the position of the infl ection point. It has been shown that ingested cholesterol accumulates to high levels in the endolysosomal compartments of these mutant cells both in vivo and in vitro but that the movement of PM cholesterol to the ER is intact under experimental conditions (19)(20)(21)(22). This is presumably because, while the effl ux of ingested 3-fold increase in 27-HC; there was no corresponding change in cellular cholesterol (not shown).…”
Section: Dependence Of 27-hc Production On the Level Of Pm Cholesterolmentioning
confidence: 99%